2002
DOI: 10.1007/bf02946070
|View full text |Cite
|
Sign up to set email alerts
|

Metabolisierung von Deoxynivalenol beim Schwein: Bestimmung von DON und DOM-1 im Urin vom Schwein

Abstract: This paper describes a feeding study with 7 pigs, which were fed with deoxynivalenol contaminated oats at a level of 0.23 mg/kg body mass/day over 16 experiment days. The contamination level of consumed feed was 14.4 mg DON/kg in the ration. The parallel control group of 7 pigs were fed with DON free oats. Urine samples were taken each two days. The content of DON and DOM-1 (de-epoxy deoxynivalenol) in urine was determined. The mean concentration of DON in urine of animals in trial group was 580 μg/l, whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…This view is further substantiated by the results of who carried out a DONbalance study and found the proportion of de-epoxy-DON of the sum of DON plus deepoxy-DON to be approximately 5 and 97% in urine and faeces, respectively. Similarly, Razzazi et al (2002) found a similar ratio of 5% for urine samples collected over 16 days from pigs fed a diet with a DON-concentration of 14.4 mg/kg. This would suggest that only a little of the gastro-intestinally formed de-epoxy-DON was absorbed and finally excreted via urine.…”
Section: Resultsmentioning
confidence: 51%
“…This view is further substantiated by the results of who carried out a DONbalance study and found the proportion of de-epoxy-DON of the sum of DON plus deepoxy-DON to be approximately 5 and 97% in urine and faeces, respectively. Similarly, Razzazi et al (2002) found a similar ratio of 5% for urine samples collected over 16 days from pigs fed a diet with a DON-concentration of 14.4 mg/kg. This would suggest that only a little of the gastro-intestinally formed de-epoxy-DON was absorbed and finally excreted via urine.…”
Section: Resultsmentioning
confidence: 51%
“…Moreover, the mentioned metabolite ratio agrees with the metabolite profile obtained from porcine urinary spot samples. Razzazi et al (2002) found a mean ratio of five percent and from the results reported by Doll et al (2003), a variation of between 3.7 and 5.4% can be calculated.…”
Section: Discussionmentioning
confidence: 68%